Thermodynamic Equilibria in Carbon Nitride Photocatalyst Materials and Conditions for the Existence of Graphitic Carbon Nitride g‑C3N4 - Botari, Tiago; Huhn, William Paul; Lau, Vincent Wing-hei; Lotsch, Bettina V.; Blum, Volker (Chemistry of materials, 2017)
We quantify the thermodynamic equilibrium conditions that govern the formation of crystalline heptazine-based carbon nitride materials, currently of enormous interest for photocatalytic applications including solar hydrogen evolution. Key phases studied include the monomeric phase melem, the 1D polymer melon, and the hypothetical hydrogen-free 2D graphitic carbon nitride phase “g-C3N4”. Our study is based on density functional theory including van der Waals dispersion terms with different experimental conditions represented by the chemical potential of NH3. Graphitic carbon nitride is the subject of a vast number of studies, but its existence is still controversial. We show that typical conditions found in experiments pertain to the polymer melon (2D planes of 1D hydrogen-bonded polymer strands). In contrast, equilibrium synthesis of heptazine (h)-based g-h-C3N4 below its experimentally known decomposition temperature requires much less likely conditions, equivalent to low NH3 partial pressures around 1 Pa at 500 °C and around 103 Pa even at 700 °C. A recently reported synthesis of triazine (t)-based g-t-C3N4 in a salt melt is interpreted as a consequence of the altered local chemical environment of the C3N4 nanocrystallites.